2017
DOI: 10.1080/00207454.2017.1288623
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted gait training in Parkinson's disease: a three-month follow-up randomized clinical trial

Abstract: RAGT may significantly improve walking ability, motor function and for a maximum period of three months. Thus, our findings support the importance of a RAGT as a valid rehabilitative tool for PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 39 publications
2
30
0
1
Order By: Relevance
“…In literature there are several important reports on the efficacy of robot assisted gait training (RAGT) on gait and other motor parameters and now it is accepted and widely applied in the rehabilitation setting of various neurological diseases (PD, MS, SCI, stroke) to improve gait [ 3 , 4 , 5 , 6 , 7 ]. However, although in rehabilitation gait and motor parameters improvement are as important as well-being and improvement in quality of life, data on well-being changes induced by RAGT are very limited and not standardized.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In literature there are several important reports on the efficacy of robot assisted gait training (RAGT) on gait and other motor parameters and now it is accepted and widely applied in the rehabilitation setting of various neurological diseases (PD, MS, SCI, stroke) to improve gait [ 3 , 4 , 5 , 6 , 7 ]. However, although in rehabilitation gait and motor parameters improvement are as important as well-being and improvement in quality of life, data on well-being changes induced by RAGT are very limited and not standardized.…”
Section: Discussionmentioning
confidence: 99%
“…As reported in other studies, body weight-supported high-intensity motor training, even with no robotic device, improved gait ability in Parkinson’s disease [ 36 ]. Since gait disability in SCI patients is usually more severe than in Parkinson’s disease, robot assistance is consequently higher [ 3 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are studies of the effects of RAGT on gait velocity with better outcomes for RAGT than the control group [1316], as well as insignificant outcomes [1719]. Some studies on PD have suggested that RAGT might improve freezing of gait, postural instability, and gait performance [1316, 20]; however, several studies have reported that RAGT is not superior to conventional therapy for improving postural instability and gait performance [17, 18, 21]. Due to the contradictory results, a well-designed study is needed to clarify the effect of RAGT on gait function in PD.…”
Section: Introductionmentioning
confidence: 99%
“…O uso de tecnologia robótica na reabilitação motora é capaz de fornecer maior repetibilidade, melhor controle de movimentos e precisão para aplicar a força desejada durante a reabilitação e realizar medições relacionadas a cinemática do movimento[25][26][27].Muitos trabalhos nesse segmento já vêm sendo desenvolvidos e direcionados a reabilitação dos sinais / sintomas motores da doença de Parkinson. Uma busca na literatura aponta que a maioria dos estudos envolvendo dispositivos robóticos na reabilitação dos sinais motores da DP são destinados a marcha, como é o caso de Furnari et al[28], Alwardart[29], Picelli et al[30] e Pilleri et al[31]. Durante a revisão da literatura foi observado que poucos dispositivos robóticos são desenvolvidos para reabilitação do membro superior em indivíduos com DP e os trabalhos encontrados nessa área focam no desenvolvimento de dispositivos robóticos para supressão de tremores, como é o caso dos trabalhos realizados por Herrnstadt[32,33], Perry[34] e Seki[35].No entanto, uma atenção especial deve ser dada ao estudo ergonômico desses dispositivos robóticos[18], uma vez que dispositivos destinados a reabilitação fisioterapêutica precisam ser projetados para adaptar-se às necessidades individuais do paciente, levando em consideração e apoiando paradigmas terapêuticos que promovam independência funcional e a avaliação da progressão da terapia.5 2.2 PARÂMETROS IMPORTANTES NA AVALIAÇÃO ERGONÔMICA DE DISPOSITIVOS ROBÓTICOSA ergonomia pode ser definida como a ciência de projetar o trabalho para se adequar ao trabalhador[36].…”
unclassified